Cystic adenoid carcinoma of the soft palate: infrequent malignant neoplasm of the salivary glands (Boletin Médico de Postgrado, 2022)
Adenoid cystic carcinoma (ACC) is a slow-growing malignant epithelial tumor that arises from the minor salivary glands, which are mainly located in the palate and the sinonasal tract. Adenoid cystic carcinoma represents approximately 3% to 6% of all salivary neoplasms and of these, only 10% originate in the minor salivary glands. It affects men and women equally, with a maximum incidence between 40 to 60 years of age. It is a slow growing tumor but its clinical course is relentless and progressive. The recommended treatment is surgical removal followed by radiation therapy, even though in selected cases the latter could be avoided (small tumors with complete removal). Recurrence rates are high for any type of tumor, with the solid form reaching rates close to 100%. The 5-year survival rates are optimistically high, but the 10 to 20-year survival rates are shockingly low. We present the case of a 57-year-old female patient who attended the Otolaryngology outpatient clinic at the Hospital Central Universitario Dr. Antonio María Pineda and showed a painless increase in volume of her left soft hemipalate of approximately 9 months of evolution. The patient underwent excision of the lesion and biopsy, which histological report is compatible with Adenoid Cystic Carcinoma (solid form). She is currently on her second year without disease recurrence.
Keywords: adenoid cystic carcinoma; soft palate; cylindroma; tumor; epithelium